1997
DOI: 10.3354/meps157307
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying hermit crab recruitment rates and megalopal shell selection on wave-swept shores

Abstract: ABSTRACT. The availability of shells has been shown to limitThe few studies of hermit crab recruitment to date

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Recruitment of these hermit crabs varies spatially across central California (S. Gaines & C. Blanchette unpubl.) and typically begins in March and ends in August, although some sites receive recruits until November (Worcester & Gaines 1997). Evidence of growth rates from congeneric species of hermit crabs shows that adult hermit crabs can grow 0.3 to 1.0 mm mo -1 (Bertness 1981) and that some species can reach maturity within 4 mo and maximum adult size within 8 mo (Fotheringham 1976b).…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment of these hermit crabs varies spatially across central California (S. Gaines & C. Blanchette unpubl.) and typically begins in March and ends in August, although some sites receive recruits until November (Worcester & Gaines 1997). Evidence of growth rates from congeneric species of hermit crabs shows that adult hermit crabs can grow 0.3 to 1.0 mm mo -1 (Bertness 1981) and that some species can reach maturity within 4 mo and maximum adult size within 8 mo (Fotheringham 1976b).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that megalopae and early juveniles of brachyuran and anomuran crabs prefer structurally complex habitats that provide refuge against predation (Fernandez et al, 1993;Dittel et al, 1996;Stevens and Swiney, 2005;Stoner, 2009). Field studies have demonstrated that the quality and quantity of empty gastropod shells strongly affect the settlement rate of marine hermit crabs (Asakura, 1991;Worcester and Gaines, 1997;Oba and Goshima, 2004). Our field surveys revealed the heterogeneous distributions of early juvenile land hermit crabs on the beach of Banda and that the distributional characteristics of juveniles were spatially stable.…”
Section: Important Habitats For Land Hermit Crabs During the Seato-lamentioning
confidence: 68%
“…The shell resource is naturally scarce in the environment and cannot always support the entire community (Vance Richard 1972aRichard , 1972bKellogg 1976Kellogg , 1977. Shells are a limiting resource for growth and reproduction (Worcester & Gaines 1997;Angel 2000). Thus, hermit crabs will constantly seek shells in the environment.…”
Section: Discussionmentioning
confidence: 99%